Production of hydroxylapatite based titania biocomposite as porous bone-like scaffold - (:unkn) unknown (International OCSCO World Press, 2015)
Purpose: In this study titania-rutile phase- was proposed as reinforcement material with Bioglass 45S5® due to its high biomcompatibility and to bioactive glass’s induced effect on fast cell regeneration and profileration.Design/methodology/approach: Porous bioinert-bioactive composite ceramics were fabricated using HA and different composition of TiO2 mixtures. Firstly 75 wt. % HA - 15 wt. % TiO2 - 10 wt. % Bioglass® 45S5 composition was prepared and another batch with changing Bioglass® content was also tried for 75 wt. % HA - 10 wt. % TiO2 - 15 wt. % Bioglass® 45S5 and H2O2 as pore former.Findings: The sample with 15 wt % TiO2 has higher hardness values and the sample with 10 wt % TiO2 have higher compressive strength values than the reference study. HA/Bioglass®/TiO2 composites are potential biomaterials to be used in bone filling and bone regeneration techniques.Practical implications: These biocomposites can be good substitute for missing or damaged bones after supplementary in vivo testing. It is also suggested to evaluate these specimens in vitro tests in SBF (Simulated Body Fluid) solution where temperature is held constant at 37°C with continuous stirring to measure if weight gain will occur by time.Originality/value: The development of improved biocompatible materials and ultimately bonelike mechanical properties is continuous task in the bioceramics research field. The use of HA is limited due to its poor mechanical properties in load-bearing applications and porous HA structures has tendency in mechanical failure. The reinforcement of HA with several inert ceramics has beneficial effect in its mechanical properties. © International OCSCO World Press. All rights reserved.
Keywords: Bioceramic composites; Biomaterials; Ceramics and glasses; Mechanical properties